DEVELOPMENT OF COMMUNICATION CULTURE IN FUTURE PRIMARY EDUCATION TEACHERS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Building a culture of communication among aspiring primary school teachers is essential to creating productive learning environments. In order to improve teacher candidates' communication abilities, this article examines a number of pedagogical approaches. It highlights the need of establishing collaborative learning environments, promoting active engagement, and incorporating reflective practices into their training. It also emphasizes the value of using technology to enhance communication skills and the necessity of culturally sensitive communication techniques to accommodate a range of student backgrounds. Teacher education programs can guarantee that aspiring teachers are ready to handle the changing demands of the classroom and improve the educational experiences of their pupils by providing them with these abilities.